STUDI ANALISIS KECERDASAN NATURALIS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK AL MISYKAAH KOTA PEKANBARU - Murni, Kurnia; Indarto, Wusono; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This descriptive study aims to determine the naturalist intelligence analysis of children aged 5-6 years in kindergarten al misykaah city of Pekanbaru. The sample in this study are educators kindergarten in the city of Pekanbaru amounting to 24 children. data collection techniques using a questionnaire containing statements about the naturalist intelligence of children aged 5-6 years in kindergarten al misykaah. Based on the results of this study concluded that the naturalist intelligence of children aged 5-6 years in kindergarten al misykaah city of Pekanbaru. in the category growing as expected 72.39%, for indicators of a child can know the kinds of plants and animals in natural conditions obtaining percentage of 72.91% with the criteria evolved according to expectations, indicators of child excited when invited to the outside of class earn a percentage 75.00% criteria evolved according to expectations, indicators of children have a natural sensitivity to obtain a percentage of 65.63% with the criteria evolved according to expectations, indicators of children can watering crops and raising animals earn a percentage 69.79% with the criteria evolved according to expectations, indicators of child enjoyed doing the project lessons based nature earn a percentage 84.37%, with the criteria developed very well, indicators of child liked to talk about animals and nature of obtaining the percentage of 66.67% with the criteria evolved according to expectations. This means shows that the intelligence anaturalis 5-6 years old children in the park kanak0kanak al misykaah developing according to expectations.Keyword: Naturalist intelligence of children